Do Peers Matter? Resistance to Peer Influence as a Mediator between Self-Esteem and Procrastination among Undergraduates - Chen, Bin-Bin; Shi, Zeyi; Wang, Yan (Frontiers in Psychology, 2016)
This study examined the relationship between self-esteem and procrastination and the mediating role of resistance to peer influence on this relationship among undergraduates. One hundred and ninety-nine Chinese undergraduate students completed the measures of procrastination, resistance to peer influence, and self-esteem. Structural Equation Modelling analyses indicated that self-esteem was negatively related to procrastination, and resistance to peer influence acted as a mediator of this relationship. The results suggest that the peer may be a key to understanding procrastination among undergraduates. Implications for future research and limitations of the current study are discussed.